The Role of the Two-Wheel Patrol Unit of the Sabhara Unit in Preventing Group War in the Makassar Police's Legal Area - Reinhard Dionisius Siga (Police Studies Review, 2021)
This research is motivated by the rise of group wars that occurred in 2018, 2019 and 2020. Therefore, efforts are needed to prevent wars between these groups. The purpose of this study is to explain the role of the Makassar Polrestabes Sabhara unit in preventing inter-group wars that occur in the Makassar Polrestabes jurisdiction and to look at the factors that influence this inter-group war. The theories used in this research are management theory, crime prevention theory, and theory performance. This research uses a qualitative approach with field research research methods. Data collection techniques are interviews, document studies and observation. The results of this study indicate that the two-wheeled patrol activities of the Sabhara Unit have not been able to carry out their roles properly. Patrol activities carried out are still not optimal due to the lack of time for implementation and insufficient members in carrying out patrol duties, especially for the prevention of group wars. For the better implementation of the role of the Sabahara patrol in preventing group war, management measures were implemented through planning, organizing, implementing and monitoring and controlling. In addition, it is necessary to look at how we focus on a crime that is trying to be prevented by using the theory of crime prevention. And we look at the factors that influence the implementation of two-wheeled patrols with the application of performance theory. Suggestions that can be given regarding the findings of this study It is hoped that the Sabhara Unit will add patrol members, especially in preventing war between groups, provide training and vocational education for Sabhara members so that they have good abilities, and check equipment and equipment for members to be carried out so that the patrol can be carried out properly.